2022
DOI: 10.3390/ph15081012
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Morin Hydrate against Attention-Deficit/Hyperactivity Disorder (ADHD) Induced by MSG and/or Protein Malnutrition in Rat Pups: Effect on Oxidative/Monoamines/Inflammatory Balance and Apoptosis

Abstract: Monosodium glutamate (MSG) is one of the most widely used food additives. However, it has been linked to protein malnutrition (PM) and various forms of toxicities such as metabolic disorders and neurotoxic effects. The current study is the first to explore the association between MSG, PM, and induced brain injury similar to attention-deficit/hyperactivity disorder (ADHD). Moreover, we determined the underlying mechanistic protective pathways of morin hydrate (MH)―a natural flavonoid with reported multiple ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 49 publications
0
7
0
2
Order By: Relevance
“…The ending number of pups was eight in all groups, except for the control group, which was 10. Rats were injected intraperitoneally with ketamine (80 mg/kg) (Salem et al, 2022) and sacrificed by cervical dislocation. Then brains were dissected out and washed with ice-cold saline.…”
Section: Experimental Designmentioning
confidence: 99%
“…The ending number of pups was eight in all groups, except for the control group, which was 10. Rats were injected intraperitoneally with ketamine (80 mg/kg) (Salem et al, 2022) and sacrificed by cervical dislocation. Then brains were dissected out and washed with ice-cold saline.…”
Section: Experimental Designmentioning
confidence: 99%
“…The study indicated a crucial role of antioxidative and anti-inflammatory mechanisms in attenuating the severity of the disease. Thus, morin improved oxidative stress parameters (by targeting Nrf2/HO-1 pathway), monoamine levels, and inflammatory status (by hindering the TLR4/NLRP3 pathway) in pups with ADHD [ 266 ].…”
Section: Antidepressant Effects Of Flavonolsmentioning
confidence: 99%
“…Masyarakat Indonesia mengkonsumsi makanan yang mengandung penyedap seperti vetsin/MSG, kaldu instan, dan bumbu masak lainnya cukup tinggi yaitu 77,6% ≥1 kali per hari (Yamin et al, 2022). Namun, MSG merupakan bahan tambahan pangan penyedap rasa yang diizinkan dengan penggunaan secukupnya dan WHO menetapkan batas maksimum penggunaan MSG yaitu 120 mg/kg berat badan per hari (Dillasamola et al, 2021;Salem et al, 2022). Penyedap rasa merupakan Bahan Tambahan Pangan (BTP) yang dapat memberikan rasa pada bahan pangan sehingga dapat bertambah manis, asam, asin, gurih, dan sebagainya (Samaun et al, 2021;Wicaks.…”
Section: Pendahuluanunclassified
“…Penyedap rasa alami diperoleh dari hewan maupun tumbuhan secara langsung atau melalui proses fisik, enzimatis, atau mikrobiologi sedangkan penyedap rasa sintetis diperoleh melalui proses kimiawi dengan bahan baku dari alam maupun hasil tambang (Tabbal, 2022;Tamaya et al, 2020). Penyedap rasa komersial sebagian besar merupakan produk hasil sintesis yang terbuat dari asam amino L atau garamnya dan 5-nukleotida (5-IMP dan 5-GMP) (Perdani et al, 2022;Tamaya et al, 2020) Garam asam amino L yang banyak digunakan sebagai bahan baku penyedap rasa makanan adalah monosodium glutamate (MSG) (Salem et al, 2022). MSG merupakan garam natrium dari asam glutamat yang dapat terurai menjadi natrium dan glutamat saat terkena air ludah, yang juga merupakan sumber natrium tinggi.…”
Section: Pendahuluanunclassified